2009
DOI: 10.1186/1477-7525-7-87
|View full text |Cite
|
Sign up to set email alerts
|

Do neurooncological patients and their significant others agree on quality of life ratings?

Abstract: IntroductionPatients suffering from brain tumours often experience a wide range of cognitive impairments that impair their ability to report on their quality of life and symptom burden. The use of proxy ratings by significant others may be a promising alternative to gain information for medical decision making or research purposes, if self-ratings are not obtainable. Our study investigated the agreement of quality of life and symptom ratings by the patient him/herself or by a significant other.MethodsPatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 23 publications
(19 reference statements)
3
35
0
1
Order By: Relevance
“…Two studies that have examined concordance using the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 instrument reported good overall agreement between patient and caregiver QOL assessments. 25,26 In accord with our findings, Sneeuw et al observed that where differences existed, they tended to be of small magnitude and reflective of less favorable QOL evaluations by the caregivers than the patients gave themselves. 25 As in our study, Giesinger et al observed poorer agreement for certain subscales yet good patientcaregiver concordance overall.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Two studies that have examined concordance using the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 instrument reported good overall agreement between patient and caregiver QOL assessments. 25,26 In accord with our findings, Sneeuw et al observed that where differences existed, they tended to be of small magnitude and reflective of less favorable QOL evaluations by the caregivers than the patients gave themselves. 25 As in our study, Giesinger et al observed poorer agreement for certain subscales yet good patientcaregiver concordance overall.…”
Section: Discussionsupporting
confidence: 90%
“…25 As in our study, Giesinger et al observed poorer agreement for certain subscales yet good patientcaregiver concordance overall. 26 Brown et al also reported strong correlations between patient and caregiver QOL reports in the only other study to our knowledge that utilized the FACT-Br instrument. 27 In a recent study by Armstrong et al that examined the congruence of malignant glioma patient and caregiver symptom reports, caregivers were observed to be adequate proxies irrespective of patient neurocognitive functioning or Karnofsky performance status.…”
Section: Discussionmentioning
confidence: 79%
“…Caregivers and health care providers are considered main candidates for the role of proxy. There are contradictory findings about QoL assessments by physicians: some studies show good patient-physician agreement (9,14,17), while others do not (3,18). On the other hand, caregivers such as a partners, parents or children may provide a more valid evaluation of the patient's QoL since they have a longer and closer contact with, and more understanding of, the patient (8,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of patients with primary brain tumours (n=42) and their significant others using the EORTC QLQ-C30 and brain cancer module, the QLQ-BN20, fairly good agreement was seen, with median correlation 0.46. 32 A recent study of the DEGRO brain module (DBM), a 10-item questionnaire rating the general condition as well as functions and impairment by symptoms in areas relevant to patients with brain metastases, found patient and proxy ratings had high correlation and similar mean changes over time, suggesting that proxies can be used as an alternative when patients are unable to self-complete questionnaires. 33 We have drawn the same conclusion from our results.…”
Section: Discussionmentioning
confidence: 99%